Geriatric Conditions and Prescription of Vitamin K Antagonists vs. Direct Oral Anticoagulants Among Older Patients With Atrial Fibrillation: SAGE-AF - McManus, David D.; Kiefe, Catarina; Lessard, Darleen; Waring, Molly E.; Parish, David; Awad, Hamza H.; Marino, Francesca; Helm, Robert; Sogade, Felix; Goldberg, Robert; Hayward, Robert; Gurwitz, Jerry; et al. (Frontiers in Cardiovascular Medicine, 2019)
Abstract Background: Geriatric conditions are common among patients with atrial fibrillation (AF) and relate to complications of oral anticoagulation (OAC). Objective: To examine the prevalence of geriatric conditions among older patients with AF on OAC and relate type of OAC to geriatric conditions. Methods: Participants had a diagnosis of AF, were aged  65 years, CHA2DS2VASC  2, and had no OAC contraindications. Participants completed a 6-component geriatric assessment that included validated measures of frailty (CHS Frailty Scale), cognitive function (MoCA), social support (MOS), depressive symptoms (PHQ9), vision, and hearing. Type of OAC prescribed was documented in medical records. Results: 86% of participants were prescribed an OAC. These participants were on average aged 75.7 (SD: 7.1) years, 49% were women, two thirds were frail or pre-frail, and 44% received a DOAC. DOAC users were younger, had lower CHA2DS2VASC and HAS-BLED scores, and were less likely to be frail. In Massachusetts, pre-frailty was associated with a significantly lower odds of DOAC vs. VKA use (OR=0.64, 95%CI 0.45, 0.91). Pre-frailty (OR=0.33, 95%CI 0.18-0.59) and social isolation (OR=0.38, 95%CI 0.14-0.99) were associated with lower odds of DOAC receipt in patients aged 75 years or older. Social isolation was associated with higher odds of DOAC use (OR=2.13, 95%CI 1.05-4.29) in patients aged 65-74 years. Conclusions: Geriatric conditions were common and related to type of OAC prescribed, differentially by age group. Research is needed to evaluate whether a geriatric examination can be used clinically to better inform OAC decision-making in older patients with AF.